Raven's Progressive Matrices, Argentinean Norms for Ages 13 to 18 and Flynn Effect - Rossi Casé, Lilia Elba (Orientación y Sociedad.)
In this study the results from Raven's Standard Progressive Matrices' administration on a sample of 1067 Argentinean students aged 13 to 18 are shown. The number of cases is proportional to the population (INDEC, 2010). For analysis purposes, 3 age groups were defined with equal 2-year intervals. Frequency distributions tend to be normal in all three groups. Observed direct scores increase with age, while variability decreases. Flynn effect is still present, fifteen years after it was observed by this research team in 2000 (Rossi-Casé, Neer & Lopetegui, 2001). In addition, average scores reached after that year show a plateau effect or stability in 15-16 and 17-18 years old groups, and a non-significant decrease in 13-14 year olds (p<.05) when compared to 2000 norms. Besides, a change in the difficulty progression between series C and D is observed. All these results are in line with similar research in other countries.